Penguatan Salbia Sebagai Alternatif Netralitas Birokrasi (ASN, Kepala Desa Beserta Perangkat Desa) Di Kecamatan Tapa Dan Kecamatan Bulango Utara - Mahmud, Ramli; Adjie, Zulfikar; Hamim, Udin; Djama, Sofyan (Universitas Pahlawan Tuanku Tambusai, 2024)
Salbia as a noble value based on customs can be used as an alternative to internalizing bureaucratic attitudes (ASN, Village Heads, village officials) to maintain neutrality in the election. Salbia is also a contextual agenda and can be practiced through modern bureaucratic practices in the narrative of local democracy. This service aims at 1) Identifying the problem of vulnerability to election violations that occur around the bureaucratic environment, 2) Building bureaucratic awareness to remain aware of the types of election violations. 3) Providing reinforcement on the application of Salbia values as an alternative to bureaucratic neutrality in the election. 4) as a means of political education to strengthen political preferences of the bureaucracy to become smart voters and actively participate in supervising the 2024 simultaneous elections. Through this service, the bureaucracy can be massively active in carrying out participatory supervision ahead of the 2024 simultaneous elections.